HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN KELENGKAPAN IMUNISASI DASAR PADA BAYI DI WILAYAH KERJA PUSKESMAS SIMPANG TERITIT KEC. WIH PESAM TAHUN 2023 - Mauliyana; Hudnah; HS, Nurlaely (Jurnal Ilmiah Cerebral Medika, 2024)
ABSTRACT Data for 2022 shows that of the 40 children who took part in immunization activities, only 10 were successful, and in 2023 immunization will decrease from 30 babies, only 6 babies are immunized. This study aims to determine the relationship between maternal knowledge and attitudes and the completeness of basic immunization in the Simpang Teritit health center working area in 2023. The research method is an analytical survey with a cross sectional approach. The research sample was mothers who had babies. The sampling technique was Total Sampling, data analysis used the chi-square test. The results of the research showed that there was a relationship between knowledge and completeness of basic immunizations for babies, with a P-value of 0.01 (P ≤ 0.05). The results of the research showed that there was a relationship between attitude and completeness of basic immunizations for babies, with a P-value of 0.01 (P ≤ 0.05). The public should seek information about immunization, because complete immunization is very important for children, not to cure but to prevent deadly diseases.Keywords : Knowledge, Attitude, Basic Immunization